PENENTUAN KUALITAS AIR SUNGAI BATANG AGAM KOTA PAYAKUMBUH BERDASARKAN PARAMETER FISIKA DAN KIMIA - Sri Agustianingsih, Maharani; Puryanti, Dwi; Purwanto, Eko (Jurnal Fisika Unand, 2025)
Research to identify the level of water quality of Batang Agam River in Payakumbuh City has been conducted based on physical and chemical parameters. Physical parameters in this study are temperature, electrical conductivity, Total Dissolve Solid (TDS), and Total Suspended Solid (TSS). Chemical parameters in this study are acidity (pH) and heavy metals in the form of cadmium (Cd), lead (Pb), and zinc (Zn). The level of river water pollution is processed using the Pollution Index (IP) method and analyzed based on the class I quality standard of Government Regulation No. 22 of 2021. The results of this study obtained that the temperature value of the Batang Agam River in Payakumbuh City in the Sumatra Region Balai Park (TBWS) area exceeds the quality standard value of 30.33⁰C. The pH and TDS values are still within the quality standard threshold of 6-9 and 1000 ppm respectively. The TSS value has exceeded the quality standard value of 40 ppm. The electrical conductivity value is still within the quality standard according to the World Health Organization (WHO) 2017 of 1500 µs/cm. The concentrations of heavy metals Cd, Pb, and Zn were 0.0495 mg/L, 0.0325 mg/L, and 0.0254 mg/L, respectively, with Cd and Pb concentrations exceeding the quality standard. Based on the measurement of water quality parameters, it is concluded that the level of pollution of the Batang Agam River in Payakumbuh City is classified as lightly polluted with an average IP value of 4.61, which cannot be used for drinking water and household purposes.